PERSEPSI KESIAPAN BERWIRAUSAHA: MINDSET WIRAUSAHA, SELF-EFFICACY, DAN MOTIVASI DIRI - Abnur, Asman; Wibowo, Agung Edy; Budhiartha, I Nyoman (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2026)
This study aims to identify differences in the perception of entrepreneurial readiness based on three main components, namely entrepreneurial mindset, self-efficacy, and self-motivation in three groups of students of the Culinary Arts, Culinary, and Room Division Study Programs. The quantitative method was used in this study with a comparative analysis design through a mean difference test. The research sample amounted to 47 students who were selected using purposive sampling techniques, with the criteria that they had taken courses in entrepreneurship, human resource management and study program practice in each learning. The results of the study show that there is a significant difference in the perception of entrepreneurial readiness between study programs. The results of the study confirm that the Culinary Study Program is considered the most prepared in terms of mindset, self-efficacy, and self-motivation because of its learning characteristics that are applicative, based on direct practice, and provide concrete experience in the production process and product innovation, the opportunity to develop products in real terms that strengthen self-confidence and give rise to higher motivation to start a business because they believe they have commodity value works in the future. These findings can be the basis for the development of a more comprehensive and equitable entrepreneurial learning strategy across vocational study programs.